Developing farmers’ community resilience in the volcanic area of Mount Merapi, Indonesia - Rozaki, Zuhud; Nuzlia, Nur Aini; Kamarudin, Mohd Fauzi; Triyono, Triyono (College of Agriculture, University of Diyala, Iraq, 2024)
Mount Merapi is one of the active stratovolcanoes in Indonesia, and its slopes are not only home to the powerful forces of nature but also to thriving communities of farmers. Many farmers' communities are found around the slopes of this mountain, relying on the fertile volcanic soil for their agricultural activities. This research was undertaken near Mount Merapi, approximately 4 km from the volcano peak, to investigate the resilience of farmers' communities in the face of Mount Merapi's potential disasters. It affects the farmer’s behavior, with the majority of residents being farmers. The primary objective of this study was to understand why and how these farmers’ communities demonstrate resilience in the wake of Mount Merapi's potential disasters. The qualitative approach was used in this research and the key informants were determined by using the purposive sampling technique. Data obtained were analyzed using an interactive data analysis model. The study identified three primary themes that significantly influenced the resilience of farmers' communities. The first theme encompasses social aspects, highlighting the importance of social capital, including strong social relations, trust, and community networks. The second theme revolves around economic factors, specifically business capital and the various forms of income within the farmers' communities. Lastly, the third theme focuses on environmental considerations, emphasizing the role of natural capital, particularly effective land use, as the most impactful in maximizing community resilience. Additionally, it was also found that the strong engagement among farmers within their communities made their resilience ability toward disaster highly formidable.